Analysis of effective management solutions through social - économic analysis and their influence on the cost of health services - Kavaldzhieva, Kalina (Тернопіль, 2014)
The social - economic analysis has resulted in detailed financial projections ( operating income and expenses applicable tariffs for water services) and the conclusions related to the implementation of the following indicators: 1) performance of financial profitability of the project -financial net present value of capital (FNPV/C), the financial internal rate of return (FRR/C), financial net present value of the investment (FNPV/K), financial internal rate of return on investment (FRR/K);2) Affordability of tariffs for water and sewerage services;3) Indicators of financial sustainability of the project (analysis of cumulative cash flow);4) Identification of the sources of funding (grants, municipal budget, loan or other credit institution).
Keywords: capital; investment; Internal rate of return; Net present value; affordability; sustainable; profitability; performance; social efficiency; terminal value; risk